Penggunaan Rokok Elektrik (Vape) Di Kalangan Perempuan Kota Pekanbaru - Andreas Pramata; Achmad Hidir (Penerbit Jurnal Indonesia, 2025)
The purpose of this study was to determine the reasons and extent of women's understanding of the risks of e-cigarettes among women in Pekanbaru City. This type of research is descriptive qualitative. Researchers analyzed data using a case study method in which researchers conducted observations, interviews and documentation. To obtain informants, researchers used the Accidental Sampling technique, which is a method of accidental sampling by taking cases or informants who happened to be there or available at the time of the study. The types and sources of data used are primary and secondary data. In this study, researchers wanted to find out the reasons why women in Pekanbaru City use e-cigarettes and whether they know the risks they will get, such as health risks, cultural risks and economic risks. Then researchers used Max Weber's theory of social action, which has 4 types of actions including instrumental actions where someone assesses the best way to achieve a goal, value actions where someone cannot assess the right or wrong method chosen, affective actions are actions taken because of emotional impulses and traditional actions which are carried out based on hereditary habits. The use of electronic cigarettes among women in Pekanbaru City was analyzed using a social action perspective. Of the 5 main informants that the researcher had interviewed, the results were that 3 informants were included in traditional actions and 2 people were included in value actions.